Evaluation of the activity of intraarticular hyaluronic acid in the repair of experimentally induced osteochondral defects of the stifle joint in dogs - Sagliyan, A.; Karabulut, E.; Unsaldi, E.; Yaman, I. (Czech Academy Agricultural Sciences, 2009)
The present study examined the results of using hyaluronic acid with autogenetic cancellous grafts in the treatment of experimentally induced osteochondral defects in the stifle joints of dogs. In this study, 10 mature dogs of different breeds, weights and of both sexes were used. General anesthesia and usual operation procedures were followed. A 10 mm deep defect was created on the femoral sulcus of the trochlea with a drill tip of 8 mm in diameter. The defects in the right and left legs were filled with autogenic cancellous grafts taken from the metaphysial region of the tibia. The left legs constituted the experimental group while the right legs served as control group. In the experimental group, 2 mg/kg intraarticular hyaluronic acid was twice administered into the stifle joint, i.e., immediately subsequent to the operation and 1 month afterwards. Parenteral antibiotics were prescribed postoperatively for ten days. Five animals were sacrificed at the third and sixth month after surgery. Macroscopic and microscopic findings obtained from each case were evaluated. On macroscopical examination, trochlear defects were determined to be incompletely filled at the third month in both control and experimental groups. On histopathologic examination, a loose fibrovascular formation in the area where the graft was applied was observed to be present in both control and experimental groups. However, in the experimental group this formation was more superficial, ossification activity was greater and trabeculous bone formation had been initiated. Macroscopical examination carried out in the sixth month determined that in the control group the defect surface did not fill up to the trochlear sulcus level. In the histopathologic examination, in control groups it was found that fibrocartilageous structures were developing in the fibrovascular space even though ossification was incomplete. The macroscopic examination showed that in the experimental group, the defect surface reached the trochlear sulcus level of defects in this month. The histopatologic examination revealed that fibrous tissue comprised a thin layer, under which ossification processes were complete and bone trabeculates fully formed. It was concluded that the usage of autogenic cancellous graft along with hyaluronic acid may be useful in the repair of large osteochondral defects.
Keywords: osteochondral defect; hyaluronic acid; dog